Instructional moves for powerful teaching in higher education - Murphy, Jeremy T.; Levinson, Meira (Cambridge, MA : Harvard Education Press, 2023)
Based on work conducted through the Instructional Moves project at Harvard University, this volume outlines the many ways in which good college and graduate school teaching is rooted in deliberate pedagogical choices that support active learning.
Includes bibliographical references and index.
ENH
Hye Trade International
Keywords: College teaching; College teaching -- Education (Higher).